Global, Regional, and National Burden of Headache Disorders, 1990–2021, With Forecasts to 2050: A Global Burden of Disease Study 2021 - GBD 2021 Headache Collaborators. Electronic address: yonkkang@gmail.com; Wijeratne, Tissa; Oh, Jiyeon; Kim, Soeun; Yim, Yesol; Kim, Min Seo; Shin, Jae Il; Oh, Yun-Seo; Jung, Raon; Kim, Yun Seo; Smith, Lee; Aalruz, Hasan; et al. (Elsevier, 2025)
Headache disorders, especially migraines and tension-type headaches (TTHs), are major global public health concerns, as shown by the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021. We provide updated global estimates of prevalence and years lived with disability (YLDs) from 1990 to 2021 across 204 countries and territories and forecasts through 2050. In 2021, there are 2.0 billion people with TTH and 1.2 billion with migraine. Although TTH is more prevalent, migraine causes higher disability. While crude prevalence and YLDs increased, age-standardized rates remained stable and are projected to continue this trend due to population growth. There is a disproportionately higher burden in women aged 30-44 and countries with higher Socio-demographic Index and Healthcare Access and Quality Index. Despite this, migraines remain underrecognized in health policies and funding. This study emphasizes the urgent need to prioritize headache disorders in global health agendas.
Keywords: disability-adjusted life years; Global Burden of Disease; headache disorders; migraine; tension-type headache; Global Burden of Disease; disability-adjusted life years; headache disorders; migraine; tension-type headache; 32 Biomedical and Clinical Sciences; 3202 Clinical Sciences; Pain Research; Brain Disorders; Women's Health; Neurosciences; Headaches; Chronic Pain; Migraines; 2.4 Surveillance and distribution; Neurological; 3 Good Health and Well Being; 32 Biomedical and clinical sciences